1974
DOI: 10.3102/0013189x003004007
|View full text |Cite
|
Sign up to set email alerts
|

Explosion of a Myth: Quantity of Schooling and Exposure to Instruction, Major Educational Vehicles

Abstract: I n the last few years, we have been inundated with repetitions of a new schooling myth. From the report on Equality of Educational Opportunity (Coleman et al., 1966) and the most recent reanalyses of its data (Mosteller and Moynihan, 1972) to the Jencks et al book onInequality (1972), we have been flooded with reports of the lack of effect of schooling. These reports have discouraged professional educators and comforted those who would reduce the resources allocated to education. Moreover, recent teachers' st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
4

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(43 citation statements)
references
References 2 publications
2
36
1
4
Order By: Relevance
“…3 However, some studies have shown a substantial relationship between these two variables (Wiley and Harnischfeger, 1974;Kidder, O'Reilly and Kiesling, 1975;Fraser, Walberg, Welch and Hattie, 1987;and Walberg, 1988). Walberg (1988) reviewed more than 100 studies and found that 88% of these showed positive influences of time on learning (Walberg, Niemiec and Frederick, 1994).…”
Section: Effectiveness Of Marginal Changes In the Amount Of Allocatedmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, some studies have shown a substantial relationship between these two variables (Wiley and Harnischfeger, 1974;Kidder, O'Reilly and Kiesling, 1975;Fraser, Walberg, Welch and Hattie, 1987;and Walberg, 1988). Walberg (1988) reviewed more than 100 studies and found that 88% of these showed positive influences of time on learning (Walberg, Niemiec and Frederick, 1994).…”
Section: Effectiveness Of Marginal Changes In the Amount Of Allocatedmentioning
confidence: 99%
“…Walberg (1988) reviewed more than 100 studies and found that 88% of these showed positive influences of time on learning (Walberg, Niemiec and Frederick, 1994). Wiley and Harnischfeger (1974) studied 6th Grade students in 40 schools in Detroit, Michigan and found that a 24% increase in time allocation lead to gains of more than a third in mathematics and verbal skills. But Karweit's (1976) analysis of the same data shows that time allocation is no longer statistically significant once differences between urban and rural settings are taken into account.…”
Section: Effectiveness Of Marginal Changes In the Amount Of Allocatedmentioning
confidence: 99%
“…This premise can be supported from at least three different perspectives. Beginning in the 1960s, researchers in education began emphasizing the importance of allocating time for learning (Carroll, 1964;Fisher et al, 1980;Wiley & Harnischfeger, 1974). Stallings (1980) regarded time on task as one of the most useful variables that came out of research on teaching in the 1970s.…”
Section: Time As a Variable In Learningmentioning
confidence: 99%
“…Theoretically, the possibility that learning takes time has been considered from at least three related perspectives-educational (Bloom, 1974;Carroll, 1964;Wiley & Harnischfeger, 1974), cognitive (Ericsson & Charness, 1994;Simon, 1990), and neural (McClelland, McNaughton, & O'Reilly, 1995)-with basic convergence on the conclusion that learning takes place within an extended time period during which information is encoded, rehearsed, elaborated, and consolidated. Walberg (1984) concluded that time was an important factor in learning, on the basis of a macro analysis of nearly 3,000 studies.…”
mentioning
confidence: 99%
“…Greenwood 199183. Bloom 1971Fisher and Berliner 1985;Gettinger 1984Gettinger , 1989Rosenshine 1979;Walberg 1988;Wang 1998;Wiley andHarnishfeger 1974 84. Frederick andWalberg 1980, 85.…”
Section: Relationships Between Instructional Time Poverty and Achiementioning
confidence: 99%